Stagnation and Revival of Kerala Economy An Open Economy Perspective - K N HARILAL, K J JOSEPH (Economic and Political Weekly June 7, 2003, 2003)
The existing literature treats the migration-remittances phenomenon as something which has tended to moderate the influence of the crisis in the Kerala economy since mid-1970s. In sharp contrast, the present paper is an attempt to bringing in the question of migration and remittances to its rightful place within the structure of the regional economy. The study attributes the stagnation in the commodity producing sectors since the mid-1970s to the `resource movement effect' and `spending effect' associated with the migration-remittances boom.